2018
DOI: 10.1016/j.eururo.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Activation of the Cation Channel TRPV4 Improves Bladder Function in a Rat Model for Detrusor Underactivity

Abstract: We demonstrate that the sensory protein transient receptor potential vanilloid 4 (TRPV4) can be targeted to improve bladder function in animals that have iatrogenic injury to the nerves innervating the bladder. Further research is required to determine whether these results can be translated to patients with an underactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…Intravesical instillation of GSK1016790, a TRPV4 agonist, induces bladder hyperactivity by reducing the threshold for bladder afferents activation . More recently, in a pelvic nerve injury rat model that exhibits phenotypic characteristics of UAB, TRPV4 agonist instillation improved the bladder function by increasing voiding frequency and reducing the postvoid residual volume . Here, we showed that old mice exhibited a downregulation of TRPV4 in the urothelium (but not in DSM and urethra), which may contribute to impaired bladder reflex.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Intravesical instillation of GSK1016790, a TRPV4 agonist, induces bladder hyperactivity by reducing the threshold for bladder afferents activation . More recently, in a pelvic nerve injury rat model that exhibits phenotypic characteristics of UAB, TRPV4 agonist instillation improved the bladder function by increasing voiding frequency and reducing the postvoid residual volume . Here, we showed that old mice exhibited a downregulation of TRPV4 in the urothelium (but not in DSM and urethra), which may contribute to impaired bladder reflex.…”
Section: Discussionmentioning
confidence: 61%
“…24 More recently, in a pelvic nerve injury rat model that exhibits phenotypic characteristics of UAB, TRPV4 agonist instillation improved the bladder function by increasing voiding frequency and reducing the postvoid residual volume. 25 Here, we showed that old mice exhibited a downregulation of TRPV4 in the urothelium (but not in DSM and urethra), which may contribute to impaired bladder reflex. TRPV4 may, therefore, play an important role in the physiopathology of UAB in aged individuals.…”
Section: Aging Induces Biochemical and Molecular Changes In Bladdermentioning
confidence: 67%
“…67,68 The demonstration of TRRV4-mediated ATP release in native bladder tissue suggests that TRPV4 can influence the physiology of the bladder. 55,64-66 TRPV4 activation evoked sustained contractions in intact bladder strips of similar magnitude to those evoked by the cholinergic agonist carbachol.…”
Section: The Basic Mode Of Action and Functional Role Of Trpv4 Recementioning
confidence: 99%
“…Thus, these findings reveal that TRPV4 activity in DSM may indeed influence bladder pathologies associated with muscle over-activity or underactivity. 67,68 The demonstration of TRRV4-mediated ATP release in native bladder tissue suggests that TRPV4 can influence the physiology of the bladder. It is currently thought that the urothelium senses distension in the bladder during filling and communicates this to the underlying tissues by release of ATP as a chemical signal.…”
Section: The Basic Mode Of Action and Functional Role Of Trpv4 Recementioning
confidence: 99%
“…Clinically, NOUR without an identifiable cause, that is, no nerve/muscle disease or damage, is classified as idiopathic, which includes many NOUR patients with unidentified functional changes in the central nervous system. Although myogenic/neurogenic animal models can be produced by bladder ischemia or pelvic nerve injury, 8,9 a recent study 10 in cats successfully produced an animal model of NOUR without nerve/muscle injury by prolonged stimulation of somatic afferent axons in the tibial nerve. This cat model of NOUR was used in the current study to determine if stimulation of the superficial peroneal nerve can reverse NOUR elicited by prolonged tibial nerve stimulation (TNS).…”
Section: Introductionmentioning
confidence: 99%